Using the project-method in interactive teaching a foreign language to students at the technical university - Ekaterina A. Rozhnova; Svetlana M. Simakova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of using the project-method in the professionally-oriented foreign language teaching at the Technical University. It is shown that using this method at foreign language classes reflects the main modern principles of teaching. They contribute to forming communicative skills and increasing motivation of foreign language teaching. The paper is focused on developmental teaching models based on individual characteristics of a person. The article describes the potential of this educational method, the stages of working with it, and also practical recommendations.